B cell depletion as a therapeutic strategy for neuromyelitis optica spectrum disorder: rationale, evidence, and challenges - Ochi, Hirofumi; Nakamura, Satoru; Nakahara, Jin (Frontiers in Immunology, 2025)
Neuromyelitis optica spectrum disorder (NMOSD) is a rare autoimmune disorder of the central nervous system that predominantly affects the spinal cord and optic nerves. Aquaporin-4 antibodies have been identified as a distinguishing biomarker of NMOSD, allowing for differentiation from multiple sclerosis and other mimicking neurological conditions. Targeted monoclonal antibody treatments are evolving based on an improved understanding of the pathophysiology underlying NMOSD. Of particular influence is the idea that NMOSD is an autoantibody-mediated disease involving B cells. The hope is that targeted treatments will improve not only outcomes but also the impact and burden of the disease on patients. This review summarizes the latest evidence for B cell pathophysiology in NMOSD and highlights the cellular and molecular mechanisms of B cell-driven disease. Finally, we focus on the mechanisms of action of B cell-targeted therapies as they relate to the mechanisms of disease.